Memorial Day - Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel., 2004)
Fearless counterterrorism operative Mitch Rapp is called upon to fight against the world's most deadly terrorists in this harrowing political thriller.